Quality of life in patients after brain meningioma resection - Pavlatou, Niki; Marvaki, Christina; Kotanidou, Anastasia; Ouzouni, Christina (Health & Research Journal, 2018)
Introduction: Lately it has been noticed an increasing interest about the quality of life that is related to the performance - effectiveness indicators and also to the objective and subjective state of patients’ health. Psychosocial problems are detected by quality questionnaires which may bother the healing process and help to the disability rate and diagnosis of the disability. Meningioma is concerned as a benign tumor which is growing slowly .Usually the relapse rates are low in total surgical excision. Aim: The aim of the present review was to explore quality of life of patients surgically treated for brain meningioma, in order to improve disease outcomes. Methodology: The methodology that was used included the review of the Greek and international literature of the last fifteen years in the databases (Pubmed, Scopus, Google Scholar,medline). The keywords that were used to search for the study were: “meningioma", “quality of life”, “SF36”, “patients” Health related quality of life”. Results: Literature review has shown that the quality of life of patients with brain meningioma depends on various factors among others the most important are location and accessibility of the tumor. The best of the treatment is not limited only to the surgical part required but it is a combination of radiation treatment for better results. When meningioma is totally surgical resected displays minimal relaplse rates in contrast to the partial resection where it reoccurs in percentage 48% during the next five years. Meningiomas that cannot be petroclival surgically such as indicate high morbidity, mortality and poor physical function. Intraventricular meningiomas remain malfuctions of vision, etc. Furthermore, a significant sign is the edema which may be associated with the aggressiveness of the tumor. Finally a possibility of reoccurrence factor is the number of mitoses in the pathological analysis. Conclusions: The quality of life of patients that had been operated with brain meningioma vary at relatively low levels and is directly related to the tumor’s localization and the choice of treatment.